Procreate-Based Material Design for Arabic Language Education: A Digital Art Approach to Interactive Learning - Segaf Baharun; Muhamad Solehudin; Sultan Abdus Syakur; Aufa Hanin Salsabil; Adham Hasif (Universitas Islam Negeri Palangka Raya, 2026)
This study investigates the pedagogical value of Procreate-based material design for Arabic language education within an Islamic boarding school. Addressing the gap in visually rich, learner-created resources for Arabic, we implemented a four-week mixed-methods intervention with 40 intermediate learners using a station-rotation model (five iPads across five groups). Procreate tasks focused on illustrated vocabulary cards, posters, and short dialogues, grounded in Multimedia Learning and constructivist principles. Quantitative results show significant vocabulary gains from pre-test (M = 62.4, SD = 8.2) to post-test (M = 79.6, SD = 6.9), t (39) = 7.81, p < .001, Cohen’s d = 0.97. Observational indicators of engagement rose 35–47.5% (e.g., peer collaboration = 92.5%, creative initiative = 70% by Week 4). Student surveys indicated high acceptance (overall M = 4.45/5), and external ratings of digital portfolios were strong (overall quality M = 8.4/10), with cultural appropriateness highest (M = 8.9). Qualitative data highlighted increased orthographic awareness, aesthetic-mnemonic effects, and peer-mentored creativity despite device constraints. Findings suggest that Procreate can transform Arabic learning from text-centered delivery to multimodal, culturally grounded creation, enhancing motivation, memory, and participation. Limitations include limited devices and short duration; implications point to scalable integration of digital art for interactive Arabic pedagogy and teacher professional development.